The dynamics of Arthropod diversity and abundance in rice field ecosystem in Central Lombok, Indonesia - Ruth Stella Petrunella Thei; Abdul Latief Abadi; Gatot Mudjiono; Didik Suprayogo (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Thei RSP, Abadi AL, Mudjiono G, Suprayogo D. 2020. The dynamics of Arthropod diversity and abundance in rice field ecosystem in Central Lombok, Indonesia. Biodiversitas 21: 5850-5857. Arthropods have roles as pests, decomposers, pollinators, and natural enemies of pests. Natural enemies play a vital role in pest population control by predation or parasitism. A study of the arthropod community in the rice field ecosystem was conducted in Central Lombok, Indonesia from December 2009 to March 2010 in order to elucidate the composition, structure, and dynamic diversity of arthropods present. Arthropod sampling was done by pitfall traps, yellow pan traps, and insect net. Arthropod dynamic diversity, especially of natural enemies, was determined by diversity index, dominance index, evenness analysis, and pictorial analysis. Based on taxonomical perspective, as many as 98 arthropod species were found, including 85 insect species from 59 families and 9 orders; and 13 spider species in 6 families. Based on the ecological functions, predator arthropods were the most common (33 species, dominated by spiders), but the phytophage arthropods had the most species richness (49.34%). A high Shannon index (3.18) and Pilou index (0.7) indicated dominant arthropods in the ecosystem. Arthropod species richness and diversity increased alongside rice development and decreased after harvest.